1989
DOI: 10.1161/01.cir.80.5.1222
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of thrombolysis with recombinant tissue-type plasminogen activator. Correlation with characteristics of and clinical outcomes in patients with acute myocardial infarction. The TAMI Study Group.

Abstract: Desire Collen, MD, PhD, and the TAMI Study Group Coagulation analysis was performed on blood samples from 386 patients with acute myocardial infarction drawn before, during, and after a continuous intravenous infusion of 150 mg recombinant tissue-type plasminogen activator (rt-PA) (Activase®). Plasma rt-PA rose to peak levels of 2.1±3.1 ,ug/ml (mean± SD). Fibrinogen levels measured by coagulation rate and by sulfite precipitation decreased from baseline levels of3.0±0.9 and 3.2+1.0 g/l, respectively, to nadir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…In patients, this effect is indirectly reflected by the correlation of blood TPA concentration with bleeding risk. 30 Once the TPA infusion is terminated, the agent is rapidly cleared 31 and at these dosages, newly induced, postinfusion trauma sites do not bleed excessively (Figure 4). The effects of plasmin can now be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In patients, this effect is indirectly reflected by the correlation of blood TPA concentration with bleeding risk. 30 Once the TPA infusion is terminated, the agent is rapidly cleared 31 and at these dosages, newly induced, postinfusion trauma sites do not bleed excessively (Figure 4). The effects of plasmin can now be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have demonstrated that the degradation products of crosslinked fibrin produced during the thrombolytic process can potentiate t-PA-induced plasminogen activation through their capacity to bind plasminogen and t-PA (7). While the major cause of t-PA-induced bleeding is likely to be lysis of fibrin within the hemostatic plug (8), the induction of the systemic lytic state may also be a contributing factor (3,4). Therefore, maneuvers that limit the systemic lytic state without impairing the thrombolytic effect of t-PA could be of potential clinical value.…”
Section: Introductionmentioning
confidence: 94%
“…Despite its affinity for fibrin, tissue-type plasminogen activator (t-PA) ' administration causes a systemic lytic state with fibrinogen proteolysis (1)(2)(3)(4). Although kinetic models predicted that high doses of t-PA would have this effect (5,6), recent studies suggest an additional mechanism through which even low doses of t-PA can produce fibrinogen breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Shiono et al 2) reported that the potential risk for anastomotic dehiscence is much higher in patients with Takayasu's arteritis than in those with dystrophic aneurysms of Marfan syndrome, even during the inactive phase of inflammation. Suzuki et al 7) emphasized the importance of reinforcing sutures around the aortic annulus and Carrel's button technique for reconstructing the coronary artery. They also recommended postoperative steroid therapy for active inflammation in patients with Takayasu's arteritis who have undergone several surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The translocated Bentall procedure might provide an alternative to composite graft detachment, 3,6,7) and might be helpful because it allows circumferential fixation outside the aortic wall and double fixation at the aortic annulus, and prosthetic valves do not apply direct pressure to the aortic annulus. Ando et al 6) noted that the pressure of valve function directly affects the rigid sewing ring in patients with AVR, which causes a higher detachment rate.…”
Section: Discussionmentioning
confidence: 99%